HUMAN RESOURCE MANAGEMENT IN THE MICE INDUSTRY: A SUSTAINABLE TRANSFORMATION APPROACH - Andi Hasbi; Wim J. Winowatan; Amiruddin Hamzah; Agus Agus (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
The MICE (Meetings, Incentives, Conferences, and Exhibitions) industry continues to grow rapidly and has a significant impact on the economy, particularly in the food and beverage (F&B) sector. Human resource (HR) management in this sector plays a crucial role in the success of events, as HR skills are directly related to service quality and participant satisfaction. This study aims to explore the skills required by HR in managing food and beverage services at MICE events and how effective HR management can enhance the success of such events. The study uses a qualitative design with surveys and case studies. Informants consist of employees working in the F&B sector who are involved in managing MICE events in Makassar and Bone Regency. Data were collected through questionnaires identifying key skills in F&B management and HR management practices implemented by organizers. Semi-structured interviews with event managers were conducted to gain deeper insights into HR management practices. Data were analyzed descriptively to evaluate the relationship between HR quality and event success. The findings show that communication skills, customer service, and managerial skills in F&B logistics are the core competencies required by HR in the MICE sector, and effective HR management can enhance participant satisfaction. Good HR management, with a focus on communication and managerial skills, has been proven to improve the success of MICE events, particularly in the food and beverage sector. This study provides new insights into the importance of HR management in the F&B sector to enhance the quality of MICE events, as well as practical recommendations for developing HR skills in this industry.